Exploring the Author’s Worldview on Social Inequality in Lan Fang’s Lelakon - Hamidah, Husnul; Ummah, Siti Rohmatul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to reveal the author's worldview in Lan Fang's novel Lelakon using Lucien Goldmann's genetic-structuralism theory, which views literary works as expressions of collective worldview. This research employs a qualitative approach with genetic-structuralism dialectical method. Data were collected through reading and note-taking techniques, then analyzed using content analysis focusing on novel structure, social environment, and author's worldview. The study reveals that Lan Fang expresses a worldview on social inequality in two main dimensions: first, economic inequality between the wealthy (bourgeoisie) and the poor (proletariat); second, gender inequality between male dominance and female subordination. The novel's structure demonstrates cultural oppositions between elite-marginal housing, employer-servant, and fantasy-reality that frame the central theme of social inequality. The novel Lelakon represents the worldview of lower social classes experiencing oppression from the bourgeois class. Lan Fang, as a Chinese-Indonesian novelist in Surabaya, expresses social criticism of economic hegemony and patriarchy through characters who undergo moral transformation in facing unbalanced social reality.